Simplistic expedient and practical synthesis of (+/-)-alpha-lipoic acid - Chavan, Subhash P.; Shivsankar, K.; Pasupathy, K. (Synthesis-Stuttgart, 2005)
Synthesis of a-lipoic acid has been achieved by a simple sequence of reactions. The synthesis highlights the use of alpha-chloroesters in a Reformatsky reaction. The intermediate keto acid is an intermediate from which both isomers of lipoic acid can be prepared.
Keywords: alpha-chloroesters; alpha-lipoic acid; Ozonolysis; Reformatsky reaction